PENGARUH PELAKSANAAN PEMERIKSAAN PAYUDARA SENDIRI (SADARI) TERHADAP PENGETAHUAN DAN KEMAMPUAN SISWI DALAM UPAYA DETEKSI DINI KANKER PAYUDARA SMA SWAKARYA TAHUN 2017 - Martha Hutapea (Jurnal Riset Hesti Medan, 2017)
Breast cancer is the second largest that attacks women in Indonesia and the number one killer in the world. One of the early detection methods of breast cancer is breast selfexamination. Most women do not do self-examination due to their lack of knowledge of breast self-examination. The objective of this research is to investigate effect of the health education of breast self-examination as an early detection for cancer on the knowledge and attitude of female students of State Vocational High School 1 of Karanganyar. This research used the quantitative pre-experimental research method with the pretestposttest design. The samples of the research were taken by using the cluster sampling technique. They consisted of 31 respondents. The data of the research were analyzed by using Wilcoxon’s test and McNemar’s Test. The result of the test shows that the value of p for the variable of Knoweldge is 0.000 and that of p for the variable of attitude is 0.000, meaning that there is an effect of the health education of breast self-examination as an early detection for cancer on the knowledge and attitude of female students of State Vocational High School 1 of Karanganyar. Therefore, the following researchers in the same field are recommended to compare between the health education with lecturing and demonstration methods and the health education with lecturing and video methods two groups, namely: Control Group and Experimental Group.